Denude the Evaluative Reason. Elements for a Philosophical-Educational Combat - Giuliano, Facundo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
These pages outline some research keys that seek to draw an interpretive horizon in relation to a critique of evaluative reason and its ethical-political implications in education. Hence the need to analyze the relationships of this type of rationality with otherness, asking us about their places and effects on educational processes. Therefore, a first definition of this rationality is proposed, in order to then characterize and deepen it critically, which will allow us to identify different ways of approaching the evaluation problem (of the other) —historically approached from views alien to the field of philosophy of education and of ethics as branches of practical philosophy. Our proposal calls into question the technical, psycho-didactic or sociological-pedagogical rhetoric’s, which for centuries has been asking what would be the best way to evaluate or directly helped to naturalize the evaluating reason. Finally, we try to think of micro-political gestures of a potential non-evaluative education and, therefore, non-fascist.